Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/europace/eux188
|View full text |Cite
|
Sign up to set email alerts
|

Cardioversion of atrial fibrillation in a real-world setting: non-vitamin K antagonist oral anticoagulants ensure a fast and safe strategy compared to warfarin

Abstract: In a real-world clinical setting with anticoagulation handled in a structured multidisciplinary AF clinic, the waiting time to cardioversion was shorter with NOACs compared to warfarin. The rates of thromboembolism and major bleeding events were low, with NOACs shown to be as effective and safe as warfarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 22 publications
4
21
1
2
Order By: Relevance
“…Gawałko et al [9] in a group of 859 patients showed that NOACs were used in 49% of patients undergoing elective cardioversion or ablation due to AF. Fredriksen et al [10] in a study of 2,150 patients hospitalised for elective cardioversion between 2011 and 2016 showed that the percentage of patients treated with NOACs was lower than in the present study, and was 32%. Also, Papp et al [11] showed that in a group of 1,101 patients, NOAC before cardioversion was used in 32% of patients.…”
Section: Discussioncontrasting
confidence: 75%
“…Gawałko et al [9] in a group of 859 patients showed that NOACs were used in 49% of patients undergoing elective cardioversion or ablation due to AF. Fredriksen et al [10] in a study of 2,150 patients hospitalised for elective cardioversion between 2011 and 2016 showed that the percentage of patients treated with NOACs was lower than in the present study, and was 32%. Also, Papp et al [11] showed that in a group of 1,101 patients, NOAC before cardioversion was used in 32% of patients.…”
Section: Discussioncontrasting
confidence: 75%
“…Strategia polegająca na podaniu jednej dawki NOAC ≥ 4 h przed kardiowersją (≥ 2 h po nasycającej dawce apiksabanu) wydaje się skuteczna i bezpieczna u pacjentów z AF trwającym ≥ 48 h pod warunkiem wykonania TEE przed kardiowersją. Alternatywą jest rozpoczęcie od razu leczenia przeciwkrzepliwego za pomocą NOAC i odroczenie kardiowersji o co najmniej 3 tygodnie [73][74][75][76][77]. Podobną strategię rozpoczęcia leczenia NOAC przed kardiowersją, z wykonaniem TEE zależnie od możliwości ośrodka lub podwyższonego ryzyka udaru u pacjenta, można stosować u chorych z AF trwającym < 48 h.…”
Section: Kardiowersja U Pacjentówunclassified
“…The 2016 ESC AF guidelines recommends the use of therapeutic oral anticoagulation at least 3 weeks before and 4 weeks after ECV [2]. The use of VKA has its limitations, the most important being its narrow therapeutic window requiring regular INR assessments, delayed onset of action and certain drug-drug interactions [11,22]. Considering these limitations, DOACs has become an attractive alternative for VKA [1].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Nowadays, DOAC is the most commonly used oral anticoagulant pericardioversion. An advantage of the use of DOAC in the setting of ECV is that it can avoid delays or postponement of ECV due to inadequate INR levels with VKA [9,11]. Avoiding postponement and rescheduling of ECV procedures by using DOAC has been shown to be cost-effective in comparison to VKA [25].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%